A work breakdown structure that integrates different views in aircraft modification projects - Garcia Fornieles, J.; Fan, Ip-Shing; Perez, A.; Wainwright, Charles E. R.; Sehdev, Kamal (Sage Publications, 2003)
The Work Breakdown Structure (WBS) defines the work scope of a project. The way a WBS is defined depends on the person and his/her viewpoint. The aircraft modification business carries out a great variety of projects. Although the core skills and tasks are similar, there are very few projects that are exact repetition of previous work. The reuse of information is difficult without a good structure to archive and manage project information. This paper presents an integrated WBS approach for managing the work scope in aircraft modification projects. The model is the result of an in-depth study and analysis of the working methods in an aircraft modification industrial company. This WBS is designed to incorporate the information needs and the views of the different functions involved in aircraft modification. It provides the structure for the reuse of information, such as cost and schedules, in the diverse range of aircraft modification projects. In this model, the top tiers of the WBS are configured from a pre-defined industry specific template. The lower tiers are defined with a flexible structure to support the different views of the knowledge users and providers in the project. The information need for all the life stages of the project is fully covered. The integrated WBS is being implemented in an enterprise wide computing solution that is used for cost estimating in the collaborating company. The same approach could be used to enhance knowledge reuse where there is a great diversity in project contracts.